The hadiths that indicate the permissibility of concluding the verse with a choice, novel and knowledge - Alsalloom, Ahmad Fares; Saouli, Jamal Farhat (Edelweiss Applied Science and Technology, 2024)
This research deals with the study of the hadiths mentioned in the Sunnah of the Prophet, which state that the reader may conclude the verse with whatever he wishes, even if it contradicts the Qur’an, for example, if the end of the verse is (Aziz Wise -) then the reader says instead (Aziz Rahim). The hadiths mentioned in this topic were graduated, and their chains of transmission were studied according to the rules of criticism in the sciences of hadith and their meanings were explained. The importance of the research lies in the fact that this issue is one of the tasks related to the narration of the Holy Qur’an, which some critics of the Holy Qur’an challenge. The research reached several results, the most important of which are: All the hadiths are weak and cannot be proven in the field of hadith criticism, however, they have possible correct meanings other than those that come to mind.